2022
DOI: 10.1111/fare.12748
|View full text |Cite
|
Sign up to set email alerts
|

Latina mothers navigating COVID‐19: Within‐ and between‐family stress processes over time

Abstract: Objective This study aimed to understand how periodic shifts in financial cutbacks and fears of contracting COVID‐19 contributed to children's externalizing behaviors due to increases in maternal stress among low‐income Latina mothers during the first 10 months of the COVID‐19 pandemic. Background The COVID‐19 pandemic caused widespread health, economic, and psychological consequences for families and children. The Latino community is particularly vulnerable to the econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…Latine immigrant families were particularly vulnerable to job losses, pay cuts, and food insecurity and were also at high risk for contracting COVID-19 due to being disproportionately employed in low-wage, essential worker jobs (Cabrera et al, 2022; Carlos Chavez et al, 2023). One study found that Latine families reported more pandemic-related stressors (e.g., parent stress, conflict) than other race/ethnic groups (Brown et al, 2020), and that the pandemic generated both economic strains and increasing worries about health of family members (Boyer et al, 2023).…”
Section: Cultural and Structural Risks In Immigrant Latine Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Latine immigrant families were particularly vulnerable to job losses, pay cuts, and food insecurity and were also at high risk for contracting COVID-19 due to being disproportionately employed in low-wage, essential worker jobs (Cabrera et al, 2022; Carlos Chavez et al, 2023). One study found that Latine families reported more pandemic-related stressors (e.g., parent stress, conflict) than other race/ethnic groups (Brown et al, 2020), and that the pandemic generated both economic strains and increasing worries about health of family members (Boyer et al, 2023).…”
Section: Cultural and Structural Risks In Immigrant Latine Familiesmentioning
confidence: 99%
“…Both qualitative and quantitative work has demonstrated that factors such as long-standing social and immigration-related inequities and experiences of discrimination shape the experiences of immigrant families including socioeconomic opportunities (e.g., Lorenzo-Blanco et al, 2017; Miller & Csizmadia, 2022). Moreover, immigrant families of color were among the most vulnerable to the health and socioeconomic repercussions of the COVID-19 pandemic (Boyer et al, 2023; Prime et al, 2020; Quandt et al, 2021).…”
mentioning
confidence: 99%
“…Lack of access to support systems may exacerbate stress they experience in relation to legal violence, bias, and other contextual factors within their lived experiences. Boyer et al (2023) found that the COVID-19 pandemic distinctly affected Latina mothers in the United States as they managed racial, gender, and class-related bias.…”
Section: Latina Mothers As Family Caretakersmentioning
confidence: 99%
“…Bruhn (2022) noted that stress Latina mothers experienced during the pandemic was heighted by their lower socioeconomic status and adversely impacted their maternal role as they aimed to “remain vigilant to protect their children from the contagious disease” (Bruhn, 2022, p. 16). However, Boyer et al (2023) and Bickham Mendez (2020) denoted Latina mothers' resiliency as they drew upon their intersectional experiences to make the most of challenges presented during the pandemic. They described how mothers found pleasure in and resourcefully used the additional time they had with their children as a result of stay‐at‐home orders during the pandemic to strengthen connections within their families.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers who engaged in more cutbacks reported higher levels of stress, depression, and anxiety (Hibel et al, 2021). Subsequent longitudinal analyses revealed a cascade by which greater financial cutbacks lead to higher children’s externalizing behaviors, through maternal stress (Boyer et al, 2023). Neither of these previous studies examined mothers’ experience of parenting or their reports of partner support.…”
Section: Stress the Pandemic And Parent–child Interactionsmentioning
confidence: 99%